Personalized Medicine for Nervous System Manifestations of von Hippel–Lindau Disease - Schunemann, Victoria; Huntoon, Kristin; Lonser, Russell R. (Frontiers in Surgery, 2016)
von Hippel-Lindau disease (VHL) is a familial neoplasia syndrome associated with multisystem tumor development. Depending on tumor type and location, current treatments for VHL-associated tumors can include a combination of chemotherapy, radiation therapy and/or surgery. Central nervous system (CNS) manifestations of VHL include craniospinal hemangioblastomas and endolymphatic sac tumors (ELSTs). While the first-line treatment for both types of VHL-associated CNS tumors is surgery, the indications for treatment are patient specific and different for each tumor type. Although early sign/symptom formation is the primary indication for resection of craniospinal hemangioblastomas, radiographic discovery (asymptomatic and symptomatic) of ELSTs can be an indication for resection of ELSTs in VHL patients. Recently, research has revealed that specific VHL germline mutations may permit targeted medical treatments of not only CNS manifestations of VHL-associated tumors but visceral tumors. Specifically, missense mutations can result in the translation of functional VHL protein (pVHL) that is rapidly degraded resulting in functional loss of the pVHL, and inhibitors of pVHL degradation may slow protein degradation and restore pVHL function. Emerging research will investigate the safety and practicality of using potential targeted therapies.